x
Info
x
Warning
x
Danger
 / 
 / 
 / 
Solve the system of equations using the inverse of the coefficient matrix. 82) -5x + 3y = 8

Question : Solve the system of equations using the inverse of the coefficient matrix. 82) -5x + 3y = 8 : 2151580

Find the inverse of the matrix (if it exists).

63) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

64) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

65) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

66) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

67) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

68) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 =

69) A =

A) A-1 =

B) A-1 =

C) A-1 =

D) A-1 does not exist.

70) A =

A) No solution

B) A-1 =

C) A-1 =

D) A-1 =

71) A =

A) A-1 =

B) A-1 =

C) No solution

D) A-1 =

72) A =

A) A-1 =

B) A-1 =

C) No solution

D) A-1 =

Find the inverse of the matrix by using a graphing calculator.

73)

A)

B)

C)

D)

74)

A)

B)

C)

D)

75)

A)

B)

C)

D)

76)

A)

B)

C)

D)

77)

A)

B)

C)

D)

78)

A)

B)

C)

D)

79)

A)

B)

C)

D)

Find B A-1.

80) A =  B =

A)

B)

C)

D)

81) A =  B =

A)

B)

C)

D)

Solve the system of equations using the inverse of the coefficient matrix.

82) -5x + 3y = 8

-2x + 4y = 20

A) x = 6, y = 2

B) x = -6, y = -2

C) x = 2, y = 6

D) x = -2, y = -6

83) 5x + 4y = 8

6x - 3y = 33

A) x = -3, y = 4

B) x = 4, y = -3

C) x = 3, y = -4

D) x = -4, y = 3

84) 3x + 5y = -10

-2x - 4y = 6

A) x = 1, y = -5

B) x = -1, y = 5

C) x = -5, y = 1

D) x = 5, y = -1

85) x + 3y = -8

-14x - 4y = -2

A) x = 1, y = -3

B) x = -1, y = 3

C) x = -3, y = 1

D) x = 3, y = -1

86) 2x + 7y - z = 9

x - 6y - 2z = -11

-4x + y + z = -7

A) x = -3, y = 1, z = 6

B) No solution

C) x = 3, y = 4, z = 1

D) x = 3, y = 1, z = 4

87) 9x - y + 7z = 106

-3x + 6y + 4z = 7

-2x - 6y + z = -32

A) No solution

B) x = 9, y = 3, z = 4

C) x = -9, y = 3, z = 18

D) x = 9, y = 4, z = 3

88) -2x - y + 4z = 12

-2x + 7z = 44

8y + z = 72

A) No solution

B) x = 6, y = 8, z = 8

C) x = 6, y = 8, z =8

D) x = -6, y = 8, z = 12

89) x - 2y + 3z = 11

4x + y - z = 4

2x - y + 3z = 10

A) x = 2, y = 3, z = 5

B) x = -2, y = -3, z = 3

C) x = 2, y = -3, z = 1

D) No solution

90) 2x + 8y + 6z = 20

4x + 2y - 2z = -2

3x - y + z = 11

A) x = 2, y = 1, z = 6

B) x = -1, y = 2, z = 1

C) No solution

D) x = 2, y = -1, z = 4

91) -4x + y + 3z - w = -9

-x - 3y + z - 4w = -4

-3x + 3y - 4z + w = 11

3x - y - z - 4w = -6

A) No solution

B) x = -1, y = -2, z = -3, w = 2

C) x = 1, y = -4, z = -5, w = 4

D) x = -1, y = 2, z = 3, w = -2

Solution
5 (1 Ratings )

Solved
Mathematics 4 Months Ago 29 Views
This Question has Been Answered!

Related Answers
Unlimited Access Free
Explore More than 2 Million+
  • Textbook Solutions
  • Flashcards
  • Homework Answers
  • Documents
Signup for Instant Access!
Ask an Expert
Our Experts can answer your tough homework and study questions
56972 Mathematics Questions Answered!
Post a Question